The Planning and Development of Islamic Education Learning for Deaf Students - Remanita, Yuan; Fathoni, Irgi Aqilul; J. Arpilleda, Alcher (Paedagogia: Jurnal Pendidikan, 2025)
Students are not interested in current learning activities because the learning is not interesting and challenging to understand. As a result, schools must plan and develop Islamic education learning for deaf students with the aim that deaf students will be more active in learning and better understand the material. This study aims to determine 1) the planning and development of syllabus workshops in Islamic education learning and 2) the planning and development of lesson plans in Islamic education learning for deaf students. This study was conducted at SLB Negeri Campurdarat Tulungagung, located at Jl. Raya Popoh No. 17, Campurjanggrang, Campurdarat, Tulungagung. Through observation, documentation, and in-depth interviews, researchers obtained various data. This study uses participatory observation data collection techniques; the data sources include the principal, elementary school teachers, high school teachers, four deaf students, and Islamic education teachers. This research uses data reduction analysis, such as Milles Hubberman analysis. Several methods were used to determine data veracity or credibility, such as considering sufficient time to collect data and continuously testing various data collection methods. The results showed that Islamic education for deaf students can be implemented well. The syllabus and lesson plans are designed flexibly and can be adjusted to the interests and needs of students to get relevant and meaningful learning experiences according to their needs.